2004
DOI: 10.1046/j.1471-4159.2003.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin is involved in depression‐like behaviour and exploratory activity

Abstract: Transthyretin (TTR), the major transporter of thyroid hormones and vitamin A in cerebrospinal fluid (CSF), binds the Alzheimer b-peptide and thus might confer protection against neurodegeneration. In addition, altered TTR levels have been described in the CSF of patients with psychiatric disorders, yet its function in the CNS is far from understood. To determine the role of TTR in behaviour we evaluated the performance of TTR-null mice in standardized tasks described to assess depression, exploratory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 39 publications
8
69
1
3
Order By: Relevance
“…A behavioral, presumably neuronal function for TTR was proposed on the basis of studies of TTR knockouts that showed ''reduced signs of depressive activity and increased exploratory activity'' (24). Our data with respect to activity levels in the animals are consistent with those findings.…”
Section: Discussionsupporting
confidence: 88%
“…A behavioral, presumably neuronal function for TTR was proposed on the basis of studies of TTR knockouts that showed ''reduced signs of depressive activity and increased exploratory activity'' (24). Our data with respect to activity levels in the animals are consistent with those findings.…”
Section: Discussionsupporting
confidence: 88%
“…and S.S.S., personal observations). In addition, the limbic forebrain of TTR-deficient mice exhibits significantly elevated levels of noradrenaline (Sousa et al, 2004), a catecholamine neurotransmitter that has been shown to modulate A␤ burden in a transgenic mouse model of AD (Kalinin et al, 2007). Finally, because retinol and thyroid hormones are essential for normal mammalian brain physiology and are particularly critical during development (Porterfield and Hendrich, 1993) and because TTR is the only thyroid hormone-binding protein found at a substantial level in the CSF (Herbert et al, 1986), it is possible that TTR reduction could cause developmental abnormalities.…”
Section: Increased Levels Of Cerebral A␤ Levels In Brains Of Hemizygomentioning
confidence: 99%
“…The products of these sequences have a variety of functions ranging from transcription factors to ion channels to a hormone transport factor. Interestingly, at least two of the factors, TTR (Stork et al 2001;Sousa et al 2004;Stein et al 2004) and NPAS2 (Garcia et al 2000), have been implicated in learning and memory.…”
Section: Learning and Memorymentioning
confidence: 99%